2017
DOI: 10.1007/s00038-017-0944-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-rated health among migrant workers: results from a population-based cross-sectional study in Almaty, Kazakhstan

Abstract: ObjectivesTo determine factors associated with SRH among migrant workers in Almaty, Kazakhstan.MethodsIn 2007, 805 vendors were screened. Approximately half were eligible (n =450), defined as at least 18 years old, a worker/owner in a randomly selected stall, having traveled 2 + hours outside of Almaty within the past year, and being an internal/external migrant. 28 non-migrants were excluded, leaving 422 participants. Logistic regression was used to examine the relationship between SRH, mental health, and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…The same is seen in the Burmese communities. Social support has been shown to lower the risk of depression and anxiety symptoms and acculturative stress Wong, Song, Leung, & Chang, 2008;Kumparatana, Cournos, Terlikbayeva, Rozental, & Gilbert, 2017). Similar findings have been published regarding social cohesion, which goes beyond the personal benefit of social support in involving workplaces and communities (Shittu et al, 2014: Hsieh, 2015.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The same is seen in the Burmese communities. Social support has been shown to lower the risk of depression and anxiety symptoms and acculturative stress Wong, Song, Leung, & Chang, 2008;Kumparatana, Cournos, Terlikbayeva, Rozental, & Gilbert, 2017). Similar findings have been published regarding social cohesion, which goes beyond the personal benefit of social support in involving workplaces and communities (Shittu et al, 2014: Hsieh, 2015.…”
Section: Discussionsupporting
confidence: 61%
“…Another socio-demographic variable associated with quality of life and mental health symptoms is self-rated physical health (Al-Maskari et al , 2011;Nadim et al , 2016). Most participants in this study rated their health as good or very good, whereas migrant workers who rated their health as fair or poor reported increased mental health problems (Britto et al, 2016;Adhikary et al, 2018;Kumparatana et al, 2017). The findings indicated that participants who rated their physical health as poor were more likely to have mental health symptoms.…”
Section: Discussionmentioning
confidence: 72%
“…Other authors have not found particular increases in alcohol abuse among migrant workers. According to Kumparatana, the vast majority did not have an alcohol problem (91%) or clinical depression (94%) [66]. Similarly, in the Bacio's study, the number of drinking occasions, total drinks per drinking episode, and number of binge drinking episodes were low among a sample of Latino day laborers.…”
Section: Alcohol and Nicotine Abusementioning
confidence: 88%
“…Hong et al [13] examined health inequalities of older rural-to-urban migrant workers (aged 45-70) in three cities of China and found that the richer were at a disadvantage in health disparities. Wu et al [2] compared older rural-to-urban migrant workers (aged 50 and above) with the middle-aged rural-to-urban migrant workers (aged [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] and young rural-to-urban migrant workers (aged [16][17][18][19][20][21][22][23][24][25][26][27][28][29], and reported that older rural-to-urban migrant workers' mental health was inferior to that of middle-aged rural-to-urban migrant workers and young rural-to-urban migrant workers. However, Hong and Wu did not compare the health status with rural counterparts.…”
Section: Introductionmentioning
confidence: 99%